Alternative routes for synthesis of N‐linked glycans by Alg2 mannosyltransferase. Issue 5 (8th January 2018) - Li, Sheng‐Tao; Wang, Ning; Xu, Xin‐Xin; Fujita, Morihisa; Nakanishi, Hideki; Kitajima, Toshihiko; Dean, Neta; Gao, Xiao‐Dong
Abstract : Asparagine (N)‐linked glycosylation requires the ordered, stepwise synthesis of lipid‐linked oligosaccharide (LLO) precursor Glc3 Man9 GlcNAc2 ‐pyrophosphate‐dolichol (Glc3 Man9 Gn2 ‐PDol) on the endoplasmic reticulum. The fourth and fifth steps of LLO synthesis are catalyzed by Alg2, an unusual mannosyltransferase (MTase) with two different MTase activities; Alg2 adds both an a1, 3‐ and a1, 6‐mannose onto ManGlcNAc2 ‐PDol to form the trimannosyl core Man3 GlcNAc2 ‐PDol. The biochemical properties of Alg2 are controversial and remain undefined. In this study, a liquid chromatography/mass spectrometry‐based quantitative assay was established and used to analyze the MTase activities of purified yeast Alg2. Alg2‐dependent Man3 GlcNAc2 ‐PDol production relied on net‐neutral lipids with a propensity to form bilayers. We further showed addition of the a1, 3‐ and a1, 6‐mannose can occur independently in either order but at differing rates. The conserved C‐terminal EX7 E motif, N‐terminal cytosolic tail, and 3 G‐rich loop motifs in Alg2 play crucial roles for these activities, both in vitro and in vivo. These findings provide insight into the unique bifunctionality of Alg2 during LLO synthesis and lead to a new model in which alternative, independent routes exist for Alg2 catalysis of the trimannosyl core oligosaccharide.—Li, S.‐T., Wang, N., Xu, X.‐X, Fujita, M., Nakanishi, H., Kitajima, T., Dean, N., Gao, X.‐D. Alternative routes for synthesis of N‐linked glycans by Alg2 mannosyltransferase. FASEB J. 32, 2492–2506 (2018). www.fasebj.org